Does grandparents' diet affect weight and risk of hypogonadism in subsequent generations?. (26th February 2015) - Chambers, Thomas; Drake, Amanda; Sharpe, Richard
Abstract: Background: Worldwide, obesity has doubled since 1980. WHO declares obesity as preventable and attributes the increase in prevalence to high consumption of energy-rich foods and decreased physical activity. Epidemiological and experimental studies suggest that parents' and grandparents' diet could also have a role. We established a model of grandparents' high-fat diet (HFD) to explore potential mechanisms. Methods: Sprague-Dawley rats were fed a HFD (45% fat) or a matched control diet (10% fat) from weaning for 14 weeks. After metabolic testing, founders (F0) were bred with controls to establish an F1 generation. F1 rats were maintained on the control diet for 14 weeks after weaning and then underwent metabolic testing followed by mating with control rats to generate F2 offspring. We analysed F0 data with ANOVA and the F1 and F2 data using mixed models, with group and sex as a fixed factor and litter as a random factor. Findings: F0 male rats (n=11–13) and female rats (n=6–12) were, respectively, 9·7% (p=0·017) and 14·7% (p=0·001) heavier after 14 weeks' HFD, with a 33·3% increase in visceral adiposity (p=0·014). F1 male and female offspring (n=6) of HFD mothers were heavier (p=0·034 and 0·01, respectively) than controls. F1 daughters of HFD fathers were also heavier (p=0·01). F2 male offspring (n=4–7) derived from HFD maternal grandfathers were 7·7% heavier (p=0·029), exhibited a 31% increase in visceral adiposity (p=0·032), a 97% increase in plasma leptin (p=0·027), a trend for lower testosterone (p=0·057), and an increase in the luteinising hormone to testosterone ratio (p=0·017). F2 male and female rats whose maternal grandfather consumed a HFD had reduced insulin sensitivity (p<0·0005). Interpretation: Our results show that founder diet affects the metabolic and reproductive health of two subsequent generations of rats in a grandparent-specific, parent-specific, and sex-specific manner. The causal mechanisms remain to be further explored. The present human obesity epidemic might thus have a wider aetiology than currently accepted. Funding: UK Medical Research Council.